Pengetahuan Sikap dan Praktek Masyarakat dalam Pengendalian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Kalumata Kota Ternate: Community Knowledge Attitudes and Practices in Controlling Dengue Hemorrhagic Fever in The Working Area of The Kalumata Health Center, Ternate City - Tomia, Sumiati; Sakriani (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Dengue hemorrhagic fever (DHF) is an acute febrile disease that can cause death and is transmitted by Aedes spp mosquitoes. Understanding the level of knowledge, attitudes and behavior of the community is an important aspect that needs to be known to design effective disease control programs. This study aims to evaluate community knowledge, attitudes and behavior regarding controlling dengue fever in the Kalumata community health center working area. A cross-sectional study was conducted in April – August 2024 in dengue endemic urban-village, namely Kalumata, Tanah Tinggi and Bastiong Talangame, Ternate City, North Maluku Province. Data was obtained through an interview method using a structured questionnaire on 100 respondents in each urbanvillage. Description of the characteristics of respondents consisting of women (74.5%), men (25.5%) with the age group 20-40 years (35.3%), 41-60 years (57.7%), >60 years (7.0%). Respondents with education levels were elementary school (14.3%), middle school (28.0%), high school (53.7%), and college (4%). The results of the analysis show that there is no relationship between knowledge and community practice in controlling dengue fever. This can be seen in the results of statistical tests with a p value = 0.187 (p value > 0.05). In contrast to attitudes, there is a significant relationship between attitudes and community practices in controlling dengue fever with a p value = 0.012 (p value < 0.05). The factor that has the most influence on dengue prevention behavior is attitude. People with a good attitude have the potential to be 2 times better in terms of dengue control practices than those who had a poor attitude.